A new species of Microcera (Nectriaceae) from Zhejiang Province, China - Feng, Xiao-Xiao; Yan, Xiao-Ni; Jin, Ying; Zhong, Zhu-Pei-Qi; Yan, Cheng-Jin; Zheng, Yong-Li (Phytotaxa, 2025)
The genus Microcera belonging to the family Nectriaceae, includes fungi that cause diseases in both fruit trees and scale insects. During our investigation of pathogens and insects on economically important plants in Zhejiang Province, China, a nectriaceous fungus with flame-like conidiomata was found associated with the bark of Rosaceae plants and the scale insect Pseudaulacaspis pentagona, which colonizes the bark. Using maximum likelihood and Bayesian inference phylogenetic analyses based on multi-locus sequence data from ITS, LSU, acl1, act, cmdA, his3, rpb1, rpb2, tef1, and tub2, we determined that this fungus clusters with M. pseudaulacaspidis, M. kuwanaspidis, and M. coccophila within the Microcera clade. Pairwise homoplasy index tests showed no significant evidence of recombination between this species and the related taxa, confirming it as a novel species. This new species, Microcera gongcheniae, is characterized by masses of orange to red, flame-like sporodochia formed on both the bark and the scale insect, as well as hyaline, cylindrical, slightly curved macroconidia formed in the sporadochia. The macroconidia of M. gongcheniae are longer than those of its sister species M. pseudaulacaspidis.